MODEL PERLAKUAN PENYIMPANAN SEBAGAI UPAYA PENYEDIAAN BENIH WIJEN BERKUALITAS (Sesamum Indicum L.) - Sulistyo Budi, Luluk; Ria Andayani, Wuye; Wahyu Pangesti, Rany (JURNAL AGRI-TEK, 2017)
All farmers desperately need quality seeds to increase their agricultural products. The aim of this research is to know the interaction of storage conditions and varieties on the viability of sesame seeds. The research method using Completely Randomized Design consisted of 2 factors and repeated 4 times. The first factor consists of: SBR 3, SBR 4, and H2 varieties. The second factor consists of: storage conditions with temperature 9C and 55% humidity in the refrigerator, storage conditions with a temperature of 30C and a humidity of 88% in a dark room, the storage conditions of temperature and humidity of 66% 33c in the room with Irradiation lamp lamp 40 watt. The parameters consisted of: weight of 1000 seeds of sesame seed (gram), seed water content (%), pH level and viability (%). Results of the analysis showed there was an interaction between the parameters of a sesame seed weight of 1000 seeds and seed moisture content for 6 weeks, the pH during 3 weeks, 6 weeks and 12 weeks, viability 9 weeks. There was a strong correlation between 1000 seed weight, moisture content and viability. Storage conditions with low temperature and low humidity of SBR 3 sesame produce 94.50% viability. Storage conditions at room temperature and high humidity SBR 4 sesame varieties yield 90.75% viability. Storage conditions with high temperature and low humidity of SBR 4 varieties produce viability of 85.25%, but susceptible to fungus fusarium sp. Keywords: sesame varieties, storage conditions, moisture content, viability.